Hubungan antara Dukungan Sosial Teman Sebaya dengan Homesickness pada Santri - Hafiz Zurrahman; Desmita Desmita (Batanang : Jurnal Psikologi, 2026)
This study aims to examine the relationship between peer social support and homesickness among students at the Diniyyah Tanjung Barulak Islamic Boarding School. Homesickness is a common psychological challenge experienced by new students due to separation from their families and home environments. Students tend to seek peer support to cope with these feelings. This study employed a quantitative correlational method using total sampling, involving 92 students as respondents. The instruments used were the peer social support scale (reliability 0.919; 44 valid items) and the homesickness scale (reliability 0.942; 27 valid items). Data analysis was performed using Pearson’s product-moment correlation with SPSS version 20. The results indicate a significant negative relationship between peer social support and homesickness (r = -0.690; p = 0.000 < 0.01). Data categorization showed that peer social support fell into the moderate category (62.0%) and homesickness into the low category (46.7%). The relative contribution of peer social support to homesickness was 47.5% (R² = 0.475). These findings confirm that the higher the level of peer social support received by students, the lower their level of homesickness. The practical implication of this study is the importance of Islamic boarding schools developing buddy system programs, peer mentoring, and counseling services to help students cope with homesickness.